RUSSIA AND EAST ASIA: NEW OPPORTUNITIES AND CHALLENGES - A. A. Kireeva (Vestnik MGIMO-Universiteta)
The article focuses on major dimensions, achievements, challenges and prospects of relations between Russia and East Asia. Strategic importance of the region is shaped by East Asia's increasing role in world politics and economy as well as by its appeal for Russia's modernization agenda. Russia's great power status rests upon the effectiveness of its East Asian policy and development model of Siberia and the Russian Far East. Russia's positions in East Asia have improved substantially over the 2000s. However, its involvement in regional economic interaction is still insignificant and Russia cannot be regarded as a full-fledged regional player in this domain. Russian-Chinese strategic partnership has been the axis of Russia's East Asian foreign policy, though overdependence on China threatens Russia's independent policy in the region and encourages Russia to search for ways to diversify its ties. Russia's national interests reside in multivector policy, aimed at developing substantive relations not only with China but also with Japan, South Korea, ASEAN (Vietnam in the first place) and India along with Russia's involvement in the resolution of Korean nuclear crisis. The rise of China and the US counter-offensive have resulted in a changing strategic environment in East Asia. A need for balancing between the US and China has brought about ASEAN countries' desire to welcome Russia as a "balancer" or an "honest player" in the region. It corresponds with Russia's course on playing a greater role in regional cooperation and integration. Russia's improving ties in political, economic, energy and security dimensions have the potential to contribute to the stability of the emerging polycentric regional order in East Asia and development of Russia's regions of Siberia and the Far East.